2013
DOI: 10.1186/1475-925x-12-111
|View full text |Cite
|
Sign up to set email alerts
|

A biometric authentication model using hand gesture images

Abstract: A novel hand biometric authentication method based on measurements of the user’s stationary hand gesture of hand sign language is proposed. The measurement of hand gestures could be sequentially acquired by a low-cost video camera. There could possibly be another level of contextual information, associated with these hand signs to be used in biometric authentication. As an analogue, instead of typing a password ‘iloveu’ in text which is relatively vulnerable over a communication network, a signer can encode a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The idea of this paper starts from Frong, Zhuang and Fister (2013). The authors describe an imagebased, biometric authentication model for hand gestures captured by video recording [9]. The gestures serve as what the authors refer to as a "biometrics password" and provide context for biometric feature extraction and biometric matching based on the "hand shape and the postures in doing those signs" [10].…”
Section: Review Of Current Biometrics Solutionsmentioning
confidence: 99%
“…The idea of this paper starts from Frong, Zhuang and Fister (2013). The authors describe an imagebased, biometric authentication model for hand gestures captured by video recording [9]. The gestures serve as what the authors refer to as a "biometrics password" and provide context for biometric feature extraction and biometric matching based on the "hand shape and the postures in doing those signs" [10].…”
Section: Review Of Current Biometrics Solutionsmentioning
confidence: 99%
“…The system accomplishes an EER that equals to 11.71% using a leap motion 3D controller for the motion acquisition process. While (Fong, Zhuang, & Fister, 2013) have utilized sign language, captured by an ordinary video camera, as hand gestures for biometric authentication system. They found that the system is able to verify individuals with maximum accuracy of 93.75%, assessing the feasibility of using gestures for authentication as well as for message communication.…”
Section: ) Hand Gesturesmentioning
confidence: 99%
“…More challenges and applications can be found e.g. in [4,7,8,12]. Of course, interaction can be done with other 3D sensors, such as the mentioned Leap Motion, an example can be found in [6] where the interaction is done with holograms for teaching technical drawing.…”
Section: Introductionmentioning
confidence: 99%